The Influence of Environmental Concern and Service Innovation on Revisit Intention at Central Market PIK–Jakarta with Destination Image as a Mediating Variable - Chrysanti, Fionna; Hanafiah , Ali (International Journal Labs, 2025)
The purpose of this study is to identify factors influencing revisit intention. The proposed research model is based on the grand theory of Tourism Systems and S-O-R, adopting the concepts of SDGs and the Triple Bottom Line (TBL). This research is further developed by examining the influence of Environmental Concern and Service Innovation on Revisit Intention at Central Market PIK, Jakarta, with Destination Image as a mediator. A quantitative approach was used with PLS-SEM (SmartPLS 4.1.1.2), and data were collected through a field survey questionnaire administered to 240 respondents who had visited and planned to return to the Central Market PIK, an urban green space in Jakarta. This instrument met the criteria of reliability and validity, with evaluation of direct and indirect influences between constructs. The results show that Environmental Concern has a positive but insignificant effect on Revisit Intention (B = 0.009; t = 0.145; p = 0.885), while Service Innovation has a positive and significant effect (B= 0.332; t = 3.466; p = 0.001). Both constructs were proven to increase Destination Image (Environmental Concern: B = 0.373; t = 6.366; p = 0.000; Service Innovation: B = 0.552; t = 11.125; p = 0.000), which in turn had a positive and significant effect on Revisit Intention (B = 0.381; t = 4.306; p = 0.000). The mediation test confirms that Destination Image fully mediates the influence of Environmental Concern (B= 0.142; t = 3.614; p = 0.000) and partially mediates the relationship between Service Innovation and Revisit Intention (B = 0.211; t = 3.988; p = 0.000). These findings confirm the role of destination image in mediating the relationship between sustainability practices and service innovation, either fully or partially, which ultimately drives revisit intentions.